A study on awareness of secondary school students around menggatal area towards Multimedia College (MMC) Sabah / Noranis Nasip Serak - Nasip Serak, Noranis (2014)
Education is defined as a process of learning that will help in the development of an individual to its fullest level besides the development of society in which both enjoy the greatest level of happiness and prosperity (Kumar & Ahmad, n.d). There are few levels of education in Malaysia starting from pre-school, primary level, secondary level and tertiary level of education (www.moe.gov.my). Tertiary education in Malaysia can be divided into public and private institution where both comprise of universities and colleges (Arokiasamy, 2011). Nowadays, the number of private colleges keeps increasing since there is a demand from students who want to further their studies. Since there are so many new established private colleges emerging, there is a possibility these colleges are not known to the public especially the students. Hence, this paper attempt to study on the level of awareness of secondary school students around Menggatal area towards Multimedia College (MMC) Sabah, one of the private colleges in Sabah. The research was done using survey technique by using questionnaire and 240 questionnaires are distributed to 240 respondents in two selected secondary school in Menggatal area which is Sekolah Menengah Kebangsaan Tebobon and Sekolah Menengah Kebangsaan Bandaraya. The result shows that many of the respondents did not know about Multimedia CoJlege (MMC) Sabah. Overall, majority of the respondent agree that Multimedia College (MMC) Sabah should do more advertisement both in printed and electronic media or can go to school for talk and therefore, they need to improve their marketing so that they will be known to the public.